Modern era fortifications as urban public places - Bukal, Grzegorz (Protection of Cultural Heritage, 2023)
The fortifications created systems of earthworks and wide moats. Their area often exceeded the area of the city surrounded by them. The loss of defensive role and the tendency of territorial growth of cities made it necessary to change the function of historical fortifications. In the 19th and 20th centuries, they were dismantled and their areas built up or transformed into public spaces. However, their development and conservation cause problems due to technical characteristics, as well as conflicts of economic, legal and administrative, urban planning, landscape, and ecological interests.